First record of the leafhopper tribe Adelungiini Baker (Hemiptera, Auchenorrhyncha, Cicadellidae: Megophthalminae) from Turkey, with notes on Achrus albicosta (Kusnezov, 1929) - Gnezdilov, Vladimir M.; Ozgen, Inanc; Emeljanov, Alexandr F.; Neimorovets, Vladimir V. (Magnolia Press, 2021)
The tribe Adelungiini Baker, 1915 is recorded for the first time from Turkey and the genus Achrus Lindberg, 1925 is recorded for the first time from China based on Achrus albicosta (Kusnezov, 1929) collected by Kozlov?s Mongol Sichuan expedition in Inner Mongolia at the beginning of last century and recently?in Eastern Anatolia, Elazi? Province. New locality records as well as illustrations of external view and male genitalia structures for A. albicosta are given from Mongolia, Kazakhstan, Turkmenistan, Uzbekistan, and Iran.
Keywords: Achrina; Central and Middle Asia; morphology; new record; Palaearctic Kingdom